In a square A B C D , E and F are the midpoints of sides A B and A D , respectively. A point G is taken on segment C F in such a way that 2 C G = 3 F G .
If the side of the square is 2 , then what is the area of △ B E G ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
GJ = 0.7 IJ, EB = 0.5 AB
Triangle BEG = 0.35 (IJ X IB)/2 = 0.35X4/2 = 0.70
Wow, a sophisticated solution! But sorry, it's too complicated. Indeed, BH = 1 + 1*[2/(2+3)] = 1.4
Here is a simpler solution. Assume the diagram as Cartesian plane. So, (1/5)(3)=0.6 Then, 2-0.6=1.4 Then, (1.4(1))/2=0.7 Answer: 0.7
You can solve for the area of △ G E B since you have already the value of I G which is the height of △ G E B , since it is an obtuse triangle with base E B .
Thus, A r e a o f △ G E B = 5 7 × 2 1
Draw two lines parallel to A B and C D through G and F and they meet B C at H and I respective.
Because △ G C H and △ F C I are similar,
C I C H = C F C G = C G + F G C G = ( 1 + 2 3 ) F G 2 3 F G = 5 3 ⇒ C H = 5 3 C I = 0 . 6
Area of △ B E G = 2 1 × B E × B H = 2 1 × B E × ( B C − C H ) = 2 1 × 1 × ( 2 − 0 . 6 ) = 0 . 7
Elegant :)
Seems rather complex.
Project G onto CD at point H and onto AB at point J.
Let x = GJ
then
GH = 2- x
Since GHD and FCD are similar right triangles the ratios of their corresponding sides are equal.
So
GH/FD=(2 - x)/1
=CG/CF
=CG/(CG + FG)
=CG/(CG + (2/3)CG)
= 3/5 = 0.6
x = 1.4
Let A = Area of BEG
A = (1/2)(GJ)(EB)
= (1/2)(x)(1)
=x/2
= 0.7
use similarity of triangles to find the height of triangle BEG and then apply 1/2 base height and find the area,
1/2 * 7/5*1 = 7/10 = 0.7
The distance from G to DC can be found by Thales' Theorem = CG/CF = 3/5. SO, the distance from G to EB is 2- 3/5 = 7/5. So, the area of BEG is 1/2 * 1* 7/5 = 7/10.
Easy Question btw :D You guys complex it Just use similarity to find XG where X belong to CD then 2 - XG = triangle BEG height = 2-0.6=1.4 area triangle BEG = 1/2 x base x height = 1.4 / 2 = 0.7 cm^2
Here, CF= sqrt(FD^2+CD^2)=>CF= sqrt(1^2+2^2)[FD= 0.5XAD=> FD= 0.5X2=> FD= 1]=>CF= sqrt(5)
Now, CG/FG= 3/2=> (CG+FG)/FG= (3+2)/2=> CF/FG= 5/2=>sqrt(5)/FG= 5/2=> FG= 2/sqrt(5)
Now, CG/FG= 3/2=> CG= (3/2)XFG=> CG= (3/2)X(2/sqrt(5))=> CG= 3/sqrt(5)
Now, imagine, we draw a perpendicular from point G upon lines AB and CD.Let, perpendicular drawn from G touches line AB at point I and perpendicular drawn from G touches line CD at point H.
Now, right triangle CFD and right triangle CGH are similar [<CDF= < CHG= 90 and <FCD= <GCH (common angle). So, <FDH= <GHC]
So, we can write, FD/GH= CF/CG=> GH= FDX(CG/CF)=> GH= 1X((3/sqrt(5))/sqrt(5))=> GH= 3/5
Now, GI= HI- GH= 2- (3/5)= 7/5
Finally, area of triangle BEG= 0.5XbXh = 0.5XBEXGI = 0.5X1X(7/5) [As, BE= 0.5XAB= 0.5X2= 1] = 7/10
Problem Loading...
Note Loading...
Set Loading...
Here is an image for better understanding of my solution:
First we need to know the length of the segment C F , by Pythagorean Theorem we obtain:
D F 2 + D C 2 = C F 2 = 2 2 + 1 2 = 5 → C F = 5
Now we need to now at what distance is the point G from points F and C , for that we can call x and y the length C G and F G respectively, then we can establish a system of equations:
( 1 ) x + y = 5
( 2 ) 2 x = 3 y
Clearing x in Eq 2 and substituting it in Eq. 1 we get:
2 3 y + y = 5
3 y = 2 ( 5 − y ) ⇒ 3 y = 2 5 − 2 y
5 y = 2 5 ⇒ y = 5 2 5
Solving for x we get: x = 5 3 5
Now, like in the image we can draw a segment parallel to D F calling the intersection with D C , I , now due to the simirality of △ F D C and △ I G C using Tales Theorem we can calculate the length of I C :
y 2 = 5 3 5 5 ⇒ y 2 = 5 3 1 = 3 5
6 = 5 y ⇒ I C = y = 5 6
So, the length of I G :
I G 2 = ( 5 3 5 ) 2 − ( 5 6 ) 2 = 2 5 4 5 − 2 5 3 6 = 2 5 9 ⇒ I G = 5 3
Now, we can almost calculate the area of △ G E B , for that we can extend the segment I G intersecting with A B at J , and a parallel segment to I C intersecting at point G and with C B at H , clearly G H J B it's a square. The area △ G H B its half of the area of the square and △ G J B ≅ △ G B H . Since I G = C H the length of H B = 2 − 5 3 = 5 7
So the area of △ B E G could be calculated substracting the area of △ G J E from the area of △ G J B :
A r e a o f △ G J B = ( 5 6 × 5 7 ) ÷ 2 ⇒ 2 5 4 2 ÷ 2 = 5 0 4 2 = 2 5 2 1
Since the length of E B is 1 and J B equals to 5 6 , the length of J B is: 5 1 . So, its area is:
( 5 7 × 5 1 ) ÷ 2 = 2 5 7 ÷ 2 = 5 0 7
Finally, the area of △ B E G is:
2 5 2 1 − 5 0 7 = 5 0 4 2 − 5 0 7 = 5 0 3 5 = 1 0 7